Pengaruh Pemberian Terapi Madu Terhadap Diare Akut Pada Anak Usia 13-35 Bulan Di Puskesmas Delitua Kecamatan Deli Serdang Tahun 2022 - Khairul Anwar; Adi Arianto; Akhmad Fatikhus Sholikh (BEST Journal (Biology Education, Sains and Technology), 2023)
Diarrhea is a condition of expenditure of the stool that is not normal or not like is usually, marked by increased volume, fluidity, as well as a frequency more than 3 times a day. The Administration of honey can be applied as a complementary therapy to the disease diarrhea. Honey can accelerate the healing in diarrheal diseases, the possibility of honey has a microbial activity of some of the reactions that form the low water activity in honey, the lower the pH and also the content of hydrogen peroxide. Hydrogen peroxide is an antiseptic compound, which makes this honey can be used as a substitute rather than antibiotics. The purpose of this research is to investigate the Effect of therapeutic honey on the frequency of diarrhea at the puskesmas delitua subdistrict Deli Serdang. Sample research as many as 16 people (control group of 8 people and the intervention group of 8 people) with sampling is purposive sampling. The research design used is a quasi-experiment research design with two group pretest and posttest control group design the data were analyzed with univariate analysis and bivariate using the Test-T. And data collected from the respondents by using the observation sheet. The results showed the Influence of the Therapy of Honey On Acute Diarrhea In a Child of Age 13-35 Months In Puskesmas Delitua Subdistrict Deli Serdang with value in the treatment group of p-value = 0.001 or a 0,05 and the control group amounted to p-value = 0.031 a 0,05. Advice for the respondents expected to consume honey after getting the therapy is the standard of the health center to accelerate the healing of diarrhea